تأثير فطريات محسنات النمو على نمو نبات الكينوا في تربة معززة بالفوسفات المحلي - السوفي, نوبة; باللموشي, منى; قدة, خديجة; غريبي, سميحة; صالحي, علي (Université of Eloued, 2022)
The importance of root fungi fungi in relation to the host plant has decome indisputable , and since such studies are rare , we tried to follow up on the previous studies , so we studied the mycorrhizal reality of quinoa plants in different soils. From the mines and phosphate company in the mountains of the neck , which is a by-product of the refinement of crude phosphates, and one of the most important results that we obtained is that the fungus improved the growth of plants by more than 38% and the phosphate in the soil reinforced with sterile organic fertilizer by more than 37% .
التنوع البيئي والمحيط
Keywords: rhizomes; host plant; فطريات جذرية، نبات مضيف